-14-3x=16+2x

Simple and best practice solution for -14-3x=16+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14-3x=16+2x equation:


Simplifying
-14 + -3x = 16 + 2x

Solving
-14 + -3x = 16 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-14 + -3x + -2x = 16 + 2x + -2x

Combine like terms: -3x + -2x = -5x
-14 + -5x = 16 + 2x + -2x

Combine like terms: 2x + -2x = 0
-14 + -5x = 16 + 0
-14 + -5x = 16

Add '14' to each side of the equation.
-14 + 14 + -5x = 16 + 14

Combine like terms: -14 + 14 = 0
0 + -5x = 16 + 14
-5x = 16 + 14

Combine like terms: 16 + 14 = 30
-5x = 30

Divide each side by '-5'.
x = -6

Simplifying
x = -6

See similar equations:

| 14=3s-4b | | x+5-5=17-5 | | log(6+x)+log(6-x)-logx=2 | | 4m^2+8m+32=0 | | 18-n/2 | | 11=3x-25 | | 10x+4x+3+6=8x+3+5x | | 12y^2+7y+10=0 | | 19x=23x+38 | | 500-11N=170 | | 3v/4=12 | | 2x+2x-14=x-9+x+2+x-7 | | -48x^5/6x | | 4.9t^2-10t+84=0 | | 5t+3=5(t+25)-22 | | (a+2)(a-5)(a+3)= | | 5t-4=44-t | | 3x^4/12x^2 | | -1/3y-4-7 | | Radx+5-radx-1=2 | | 9z+15=8z+12 | | Sinxcosy=7x^2 | | 5x+10=8x+10 | | 15=8-(z+10) | | 42/4a=4 | | 3m-2/3=211/3 | | 6x-1=11+5 | | X-3=3+3x | | 4/5p=3 | | -5(3+r)=30 | | -6.8+4.24=x | | y=1/3x1-2 |

Equations solver categories